Approximate controllability for a class of hemivariational inequalities. (April 2015) - Liu, Zhenhai; Li, Xiuwen
Abstract: In this paper, we deal with the approximate controllability for control systems described by a class of hemivariational inequalities. Firstly, we introduce the concept of mild solutions for hemivariational inequalities. Then the approximate controllability is formulated and proved by utilizing a fixed-point theorem of multivalued maps and properties of generalized Clarke subdifferential.